Pengaruh Kualitas Pelayanan terhadap Kepuasan Nasabah Perbankan Syariah - Astri Ayu Purwati; Zulfadli Hamzah (COSTING : Journal of Economic, Business and Accounting, 2019)
In the last few years, Islamic banking in Indonesia has shown a positive development which is shown through the addition of Islamic banks in Indonesia. To increase its market share, Islamic banking needs to analyze what factors influence the community to be willing to become customers in Islamic banks, one of which is through service quality. This study aims to examine the effect of service quality on customer satisfaction of Islamic banks in the city of Pekanbaru. The research method used is multiple regression analysis where the sample used in this study was 200 customers. The results showed that overall dimensions of service quality have a significant positive effect on customer satisfaction, which means that the better the quality of service starting from physical evidence, responsive data, reliability, assurance and empathy provided by Islamic Banking will be able to increase customer satisfaction and vice versa. Keyword : Service Quality, Satisfaction, Syaria Bank